Prevalensi Penyakit Infeksi Menular Lewat Transfusi Darah (IMLTD) Darah Donor di UDD PMI Kota Surabaya Tahun 2018-2022 - Ariani, Nia Lukita; Sudiwati, Ni Luh Putu Eka; Panggayuh, Ardi; Widuri, Sasi (Universitas Tribhuwana Tunggadewi, 2024)
Transmission of infectious diseases is one of the risks in the blood transfusion process. The Blood Donor Unit (UDD), as a blood provider institution, must ensure that blood products distributed in the community are safe, especially from infectious diseases that can be transmitted through blood transfusion (TTI). UDD PMI Surabaya is a first-class UDD and CPOB-certified facility that serves blood needs not only in East Java but also as a reference for the Eastern Indonesia region. The location of UDD is in a big city, the number of donors is quite large, the coverage of the area of origin of donors and the target users of blood products is quite broad, and a complete screening test method are interesting factors to study regarding the prevalence of TTI disease. This study aims to determine the prevalence of infectious diseases transmitted through blood transfusion among blood donors in UDD PMI Surabaya in 2018–2022, as well as the sociodemographic characteristics of reactive donors. This research is a retrospective, descriptive study. Data for 2018–2022 comes from the in UDD PMI Surabaya database with total number of 639580 blood donors. The research results show that hepatitis B is a TTI disease with the highest prevalence compared to other TTI diseases. Most donors come from the 17–30 year age group who have reactive TTI test results, and this decreases with increasing age except for hepatitis B. Reactive donors are more dominated by women than men, except for HIV disease.